ANALYSIS OF DIGITAL-BASED CASH WAQF MANAGEMENT STRATEGIES (SHARIA-BASED CROWDFUNDING PLATFORMS) AS AN INSTRUMENT FOR UNIVERSITY MANAGEMENT - Tika Kartika Kartika; Ahmad Mulyadi Kosim; Nadilla (JPG: Jurnal Pendidikan Guru, 2026)
This research seeks to examine the management strategies of digital cash waqf via Sharia-compliant crowdfunding platforms as an alternative means for financing the development of university infrastructure. The constraints of university budgets for infrastructure necessitate innovative funding solutions that are both sustainable and compliant with Sharia principles. This study uses a qualitative approach with a descriptive-analytical design. This approach was chosen to explore in depth the mechanisms, challenges, and strategies of digital-based cash waqf management. Data collection techniques were carried out through library research (including a normative/doctrinal legal approach/research, supported by statutory analysis and intpretaion of legal document) and documentation (financial reports, digital platforms, and related documents on cash waqf management), followed by a comparison of articles at the national level and a comparison of the research results with similar studies in other countries to increase global relevance. When compared to conventional approaches, digital cash waqf offers notable benefits in terms of accountability, transparency, and a larger donor base. However, there are obstacles to the implementation, including issues with public trust, low digital literacy among Nazhirs (waqf managers), and regulatory gaps. The study develops a strategic framework that incorporates Nazhir professionalism certification, digital payment ecosystems, and cooperative marketing aimed at millennial donors. In conclusion, platforms for sharia-based crowdfunding act as a strategic catalyst for maximizing the potential of cash waqf. By putting these digital strategies into practice, universities' independence in building infrastructure can be effectively supported, guaranteeing long-term educational sustainability.